Delivery of oligonucleotide‐based therapeutics: challenges and opportunities - Suzan M Hammond; Annemieke Aartsma‐Rus; Sandra Alves; Sven E Borgos; Ronald A M Buijsen; Rob W J Collin; Giuseppina Covello; Michela A Denti; Lourdes R Desviat; Lucía Echevarría; Camilla Foged; Gisela Gaina; et al. (EMBO Molecular Medicine)
Abstract Nucleic acid‐based therapeutics that regulate gene expression have been developed towards clinical use at a steady pace for several decades, but in recent years the field has been accelerating. To date, there are 11 marketed products based on antisense oligonucleotides, aptamers and small interfering RNAs, and many others are in the pipeline for both academia and industry. A major technology trigger for this development has been progress in oligonucleotide chemistry to improve the drug properties and reduce cost of goods, but the main hurdle for the application to a wider range of disorders is delivery to target tissues. The adoption of delivery technologies, such as conjugates or nanoparticles, has been a game changer for many therapeutic indications, but many others are still awaiting their eureka moment. Here, we cover the variety of methods developed to deliver nucleic acid‐based therapeutics across biological barriers and the model systems used to test them. We discuss important safety considerations and regulatory requirements for synthetic oligonucleotide chemistries and the hurdles for translating laboratory breakthroughs to the clinic. Recent advances in the delivery of nucleic acid‐based therapeutics and in the development of model systems, as well as safety considerations and regulatory requirements for synthetic oligonucleotide chemistries are discussed in this review on oligonucleotide‐based therapeutics.